Analysis of Planning and Drug Procurement at Kragan II Public Health Center during Covid-19 Pandemic - Maulidiyyah, Fitrotul; Rahardjo, Bambang Budi (Journal of Public Health for Tropical and Coastal Region, 2022)
Introduction: Based on the results of a preliminary study at the Kragan II Health Center, Kragan District, Rembang Regency, it was found that problems in drug procurement activities were located on the Large Pharmaceutical Trader or Pedagang Besar Farmasi (PBF). In addition, the COVID-19 pandemic has also affected the budget cuts for the procurement of drugs at the Kragan II Health Center.Methods: This research was descriptive qualitative research. Data collection techniques use in-depth interviews and observation techniques. The sampling technique used was purposive sampling and data were analyzed using the Miles and Huberman model.Results: The results showed that the process of planning and supplying drugs at the Kragan II Health Center had not gone well even though the indicators in Regulation of the Minister of Health Number 74 of 2016 of the Republic of Indonesia had been realized. The process of planning and procuring drugs at the Kragan II Health Center (Puskesmas) experienced problems in the field of funding for the procurement of drugs due to the Covid-19 pandemic. Another problem is the PBF whose response is slow and the drugs distributed are not following what was ordered by the pharmacist.Conclusion: Regarding debts with PBF, pharmacists are advised to discuss with the Head of the Kragan II Health Center regarding budget priorities during the COVID-19 pandemic to immediately pay off debts with PBF so that pharmacists can procure with PBF again. Therefore, drug services to patients can run well.